Tribological performance of Graphene/Carbon nanotube hybrid reinforced Al2O3 composites - Yazdani, Bahareh; Xu, Fang; Ahmad, Iftikhar; Hou, Xianghui; Xia, Yongde; Zhu, Yanqiu (Nature Publishing Group, 2015)
Tribological performance of the hot-pressed pure Al2O3 and its composites containing various hybrid contents of graphene nanoplatelets (GNPs) and carbon nanotubes (CNTs) were investigated under different loading conditions using the ball-on-disc method. Benchmarked against the pure Al2O3, the composite reinforced with a 0.5 wt% GNP exhibited a 23% reduction in the friction coefficient along with a promising 70% wear rate reduction, and a hybrid reinforcement consisting of 0.3 wt.% GNPs + 1 wt.% CNTs resulted in even better performance, with a 86% reduction in the wear rate. The extent of damage to the reinforcement phases caused during wear was studied using Raman spectroscopy. The wear mechanisms for the composites were analysed based on the mechanical properties, brittleness index and microstructural characterizations. The excellent coordination between GNPs and CNTs contributed to the excellent wear resistance property in the hybrid GNT-reinforced composites. GNPs played the important role in the formation of a tribofilm on the worn surface by exfoliation; whereas CNTs contributed to the improvement in fracture toughness and prevented the grains from being pulled out during the tribological test.